2022
DOI: 10.3399/bjgp.2022.0241
|View full text |Cite
|
Sign up to set email alerts
|

Patient experience and satisfaction with symptomatic faecal immunochemical testing: an explanatory sequential mixed-methods evaluation

Abstract: Background: Recent evidence suggests that faecal immunochemical testing (FIT) can rule out colorectal cancer in symptomatic adults. To date, there is little research exploring experiences of FIT for this population. Aim: To explore patient experience and satisfaction with FIT in an ‘early adopter’ site in England. Design: We used an explanatory sequential mixed-methods approach combining mailed quantitative surveys with semi-structured telephone interviews. Methods: Multivariate logistic regression was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(37 reference statements)
0
6
0
Order By: Relevance
“… 36 There were also suggestions around who research should be carried out with, such as patients who are not referred to secondary care, 48 family members, 34 41 primary care HCPs, 31 32 34 36 41 47 52 57 specific population subgroups 36 and members of the community. 43 In terms of topics for future research, suggestions included exploring HCP consultation behaviour 41 and how to improve patient HCP communication, 30 sometimes with a focus on inequality 44 46 ; best practice for safety netting 56 ; comparing patient and HCP symptom perception 40 41 ; researching ways to improve the cancer care pathway. 33 42 52 55 56 This may include ways of accessing diagnostic tests 37 52 ; exploring quantitatively the impact of the diagnostic route 53 ; investigating why some patients present at the emergency department 51 and the role of health literacy 49 and GP characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 There were also suggestions around who research should be carried out with, such as patients who are not referred to secondary care, 48 family members, 34 41 primary care HCPs, 31 32 34 36 41 47 52 57 specific population subgroups 36 and members of the community. 43 In terms of topics for future research, suggestions included exploring HCP consultation behaviour 41 and how to improve patient HCP communication, 30 sometimes with a focus on inequality 44 46 ; best practice for safety netting 56 ; comparing patient and HCP symptom perception 40 41 ; researching ways to improve the cancer care pathway. 33 42 52 55 56 This may include ways of accessing diagnostic tests 37 52 ; exploring quantitatively the impact of the diagnostic route 53 ; investigating why some patients present at the emergency department 51 and the role of health literacy 49 and GP characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…After deduplication and removal of studies which did not meet the inclusion criteria, 18 studies remained. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] In the grey literature search, six reports were assessed for inclusion, and three were retained. [47][48][49] Six papers were included following the citation and references search.…”
Section: Study Selectionmentioning
confidence: 99%
“…Previous research has shown that patient satisfaction with symptomatic FIT is high, 17 however a paucity of research exists examining the accurate completion of submitted FIT samples. Two previous studies from the USA showed FIT rejection rates between 17% and 42% in asymptomatic (screening) populations.…”
Section: Discussionmentioning
confidence: 99%
“…Since symptomatic populations have varied (and higher) levels of risk compared with an asymptomatic screening population, evidence on the patients’ experience of care when and after doing FIT is crucial. To our knowledge, only two other studies have reported on symptomatic patients’ views of FIT; one quantitative study focusing on usability and acceptability,27 and one mixed-methods study evaluating patient experience and satisfaction 29…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only two other studies have reported on symptomatic patients’ views of FIT; one quantitative study focusing on usability and acceptability, 27 and one mixed-methods study evaluating patient experience and satisfaction. 29 …”
Section: Introductionmentioning
confidence: 99%